The Interface Between Competition Law and Data Protection : The Need for A More Integrated Approach - Nasarudin Abdul Rahman; Ria Setyawati (Universitas Airlangga, 2026)
This article examines the growing interface between competition law and data protection in the digital economy, where large platforms accumulate vast datasets that raise both antitrust and privacy concerns. Using a qualitative doctrinal and comparative legal approach, this study analyzes legal developments in the EU, Germany, Malaysia and Indonesia to highlight tensions and complementarities between the two regulatory regimes. The paper finds that data-driven market dominance requires regulators to assess practices such as self-preferencing, refusal to supply, and exploitative data processing through both privacy and competition lenses. Case analyses from Facebook and Google illustrate how dominance in digital ecosystems can harm users and stifle competition. In the Malaysian context, the article critiques the limitations of the current legal framework, including the Competition Act 2010 and PDPA 2010, and calls for integrated regulatory reforms. In the Indonesian context, the analysis focuses on the application of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, which, despite not explicitly regulating data, provides an effects-based framework to address data-driven market power, self-preferencing, refusal to supply, and exploitative conduct in digital markets. The findings advocate for a balanced, coordinated framework that addresses the complexities of data governance while fostering innovation, fairness, and user autonomy.